A Sociological Model of Culture-Based Innovation Capacity in the Lasem Batik Artisan Community - Qisthi Maghfiroh; Sunarmi; M. Arif Jati Purnomo (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The sustainability of culture-based creative industries depends not only on adaptation to environmental change but also on innovation capacity generated within cultural communities. Although previous research on Lasem Batik has examined history, heritage preservation, and the creative economy, the sociological mechanisms that construct and sustain innovation capacity remain insufficiently explained. This study develops a Sociological Model of Culture-Based Innovation Capacity (MSKIBB) by examining the relationships among artisans’ motivation, technical and creative capabilities, human resources, culture and tradition, and visual identity in the Lasem Batik artisan community. A qualitative case study design was employed. Primary data were collected through participant observation and semi-structured interviews with artisans, entrepreneurs, community leaders, cultural practitioners, academics, and policymakers selected through purposive and snowball sampling. Secondary data were obtained from archives, government documents, and scholarly literature. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, conclusion verification, and open, axial, and selective coding. The findings show that innovation capacity emerges from five mutually reinforcing dimensions: motivation initiates creative action; technical and creative capabilities transform ideas into products; human resources sustain intergenerational knowledge transfer; culture and tradition provide normative legitimacy; and visual identity strengthens differentiation while preserving authenticity. The MSKIBB advances innovation sociology by conceptualizing innovation capacity as a socially embedded and culturally constructed phenomenon and offers practical guidance for community empowerment and the sustainable development of culture-based creative industries.